Process Development and Analysis of Electromagnetic Multi-Spot Joining of AA5052 Sheets - Ummed Singh; Ashish Rajak; Taeseon Lee (Metals, 2023)
In this study, two sheets of AA5052 are joined with the high-strain-rate multi-spot joining process using an electromagnetic system. While producing a single spot joint by electromagnetic joining (EMJ) is common, the distribution and application of the pressure can be modified by the design of the coil and spacers to make multiple joints at once. When a preformed dimple is used to provide the standoff distance, it can eliminate the need for spacers and provide good aesthetics for the final product. In the current study, a joint design is developed to provide three spot joints coincidentally by a single discharge of a capacitor bank. For the experiment, four distinctive discharge energies were used for joining: 7, 8, 9, and 10 kJ. The most successful joint sample was made by 8 kJ and was tested for mechanical properties. The cross-section was observed in order for us to understand the joint quality produced by the process. It was found that the ”I”-shaped rectangular coil produces a variable magnetic flux, leading to different flyer deformation variations in the joint geometry. At the centre of the ”I” coil, the minimum flux was predicted, leading to lesser sheet forming, hence a weaker centre-spot joint strength. Further, a numerical study is performed to find the Von Mises stresses, equivalent plastic strain, impact velocity, and impact pressure on the sheets. This manuscript provides new information regarding coil designing and the changes that could be further made to improve the electromagnetic sheet multi-spot joining process.